2002
DOI: 10.1002/cne.10449
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional asymmetry in the normal and epileptic rat dentate gyrus

Abstract: The rat dentate gyrus is usually described as relatively homogeneous. Here, we present anatomic and physiological data which demonstrate that there are striking differences between the supra-and infrapyramidal blades after status epilepticus and recurrent seizures. These differences appear to be an accentuation of a subtle asymmetry present in normal rats. In both pilocarpine and kainic acid models, there was greater mossy fiber sprouting in the infrapyramidal blade. This occurred primarily in the middle third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 61 publications
9
97
2
1
Order By: Relevance
“…Thus, using the methods in the current study, previous studies have shown that status, even when truncated by anticonvulsants, damages neurons in forebrain [15,21]. An alternate explanation is that the motor neurons expressed VEGF as a response to insult or injury.…”
Section: Vegf Upregulation: a Response To Seizure-induced Injury mentioning
confidence: 79%
“…Thus, using the methods in the current study, previous studies have shown that status, even when truncated by anticonvulsants, damages neurons in forebrain [15,21]. An alternate explanation is that the motor neurons expressed VEGF as a response to insult or injury.…”
Section: Vegf Upregulation: a Response To Seizure-induced Injury mentioning
confidence: 79%
“…NPY expression was found markedly increased in hilar GABAergic interneurons, granule cells and sprouted mossy fibers (Bellmann et al, 1991;Chafetz et al, 1995;Lurton and Cavalheiro, 1997;Scharfman et al, 1999Scharfman et al, , 2002Sperk et al, 1992;Takahashi et al, 2000;Vezzani et al, 1996). NPY in the dentate gyrus can influence synaptic transmission and neurogenesis, demonstrates remarkable plasticity after seizures (Scharfman and Gray, 2006), and may have an anticonvulsive action (Furtinger et al, 2001;Klapstein and Colmers, 1997;Vezzani et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In normal animals, proliferating cells labeled with the mitotic marker bromodeoxyuridine (BrdU) are restricted to the SGZ of the hippocampus. In contrast, following seizure activity BrdU+ cells were found extensively in the dentate hilus and/or dentate molecular layer of the hippocampus, indicating aberrant migration of dividing cells in response to seizure-induced cell loss (Parent, et al, 1997, Scharfman, et al, 2000, Scharfman, et al, 2002, Parent, et al, 2006. Similarly, displaced granule cells have been observed in hippocampal tissues obtained from patients with TLE (Houser, 1990, Thom, et al, 2002, Liu, et al, 2008.…”
Section: Temporal Lobe Epilepsymentioning
confidence: 99%